Concept study of micro-architectural elements of street businesses in Pulau Tuba - A Wafiy Haniff Kamal,; Azimin Samsul Mohd Tazilan,; Kamarul Afizi Kosman,; Sharmiza Abu Hassan,; Sharina Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The purpose of this paper is to identify the elements of street business microarchitecture (MCR) in rural areas, namely Tuba Island, Langkawi, and its significance in the local economy. The impact of Covid-19 leads to a trend of Malaysian youth who had previously migrated to the city are returning to the countryside. Hence, it encourages a better understanding of urban sustainability through classification, design, and intervention in rural areas of Malaysia using case studies from Tuba Island, Langkawi. This study uses a qualitative research approach and literature review, by recording the presence of active structure of MCR of the street businesses and the scenarios that occur in the specific area and identifies the type of microarchitecture classification based on previous studies. Interviews and observation approaches were implemented to obtain comprehensible information to gather data, which were then used in the analysis. This study finds that MCR units that are available at Pulau Tuba are mainly permanent and semi-permanent status and can be found on main roads and places of commercial activities with many visitors. MCR typoscape T8 are mostly restaurants and grocery stores, while T3, T4 and T5 are suitable for small island use as they are remote, easy to set up and ad-hoc but fixed setting.